Outcome Comparison of Stapled Versus Hand-Sewn Anastomosis in Elective Gastrointestinal Surgeries: Stapled Versus Hand-Sewn Anastomosis in Elective Gastrointestinal Surgeries - Tariq Ghafoor, Muhammad; Sabir, Sohail; Tumrani, Rukhsana; Kauser, Noreen; Haider, S. Sabahat (Pakistan Journal of Health Sciences, 2022)
Bowel loop anastomosis is considered as major part of elective gastrointestinal surgeries. The anastomotic procedures being used now a days include hand sewn and stapled anastomosis. For appropriate gastrointestinal anastomosis, many factors should be considered such as intraoperative duration, restoration of blood supply, restoration of normal function of gastrointestinal tract and decrease tissue damage. Objective: The objective of the study was to compare the outcome of stapler and hand sewn anastomosis in elective gastrointestinal surgeries. Methods: Cross-sectional observational study conducted in department of surgery, Sheikh Zayed Hospital, Rahim Yar Khan from May 1, 2021 to August 31, 2022. Total 60 patients included in study and outcome variables such as anastomotic integrity, duration of procedure, post-operative hospital stay and return of bowel activity compared in hand sewn and stapled anastomosis. Results: The study included total 60 patients out of which 38 (63.33%) underwent stapled anastomosis and 22 (36.66%) underwent hand sewn anastomosis. Age (P value: 0.373), gender (p value: 0.372), anastomotic site (p value: 0.284) and return of bowel activity (p value: 0.331) did not show statistically significant difference between two groups. Anastomotic integrity (p value: 0.025), duration of procedure (p value: 0.002), post-operative hospital stay (p value: 0.037) show statistically significant difference between hand sewn and stapled anastomosis. Conclusions: Stapled anastomosis has better anastomotic integrity, reduced duration of procedure and decreased post-operative hospital stay as compared to hand sewn anastomosis with statistically significant difference between two groups.